Horses’ (Equus Caballus) Laterality, Stress Hormones, and Task Related Behavior in Innovative Problem-Solving - Laureen Esch; Caroline Wöhr; Michael Erhard; Konstanze Krüger (Animals, 2019)
Domesticated horses are constantly confronted with novel tasks. A recent study on anecdotal data indicates that some are innovative in dealing with such tasks. However, innovative behavior in horses has not previously been investigated under experimental conditions. In this study, we investigated whether 16 horses found an innovative solution when confronted with a novel feeder. Moreover, we investigated whether innovative behavior in horses may be affected by individual aspects such as: age, sex, size, motor and sensory laterality, fecal stress hormone concentrations (GCMs), and task-related behavior. Our study revealed evidence for 25% of the horses being capable of innovative problem solving for operating a novel feeder. Innovative horses of the present study were active, tenacious, and may be considered to have a higher inhibitory control, which was revealed by their task related behavior. Furthermore, they appeared to be emotional, reflected by high baseline GCM concentrations and a left sensory and motor laterality. These findings may contribute to the understanding of horses’ cognitive capacities to deal with their environment and calls for enriched environments in sports and leisure horse management.